IMPROVING STUDENT SCIENCE LEARNING OUTCOMES THROUGH COOPERATIVE LEARNING: EARLY CHILDHOOD STUDENTS THROUGH SMALL GROUPS - I Made Citra Wibawa (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2023)
The cooperative learning model is one of the learning models currently being developed. This learning model is expected to change and direct students to be better. The purpose of this research is to compare the effect of cooperative learning and conventional learning in their effect on the learning outcomes of elementary school students. This research is a quasi-experimental involving two groups of samples taken randomly. This research involved a sample of 39 grade V elementary school students in clusters 1 and 2 of Marga. Students' science learning outcomes were captured using essay tests and analyzed using independent group t-tests. The results showed that there was a statistically significant effect of cooperative learning and conventional learning on students' science learning outcomes. Thus, cooperative learning is the right learning to use in improving the learning outcomes of elementary school students.